An application of the augmented Solow model to measure the impact of military spending on economic growth in Uganda for the period 1962-2018. - Abura, Elijah (School of Economics, 2022)
This paper provides a case study of the impact of military spending on economic growth in Uganda using an exogenous dynamic growth model and time-series data over the period 1962-2018. This is achieved by estimating and appraising a sample inclusive of periods not covered in previous studies that resulted in structural changes to the Ugandan economy such as conflict and currency devaluations. The results indicate that there is a significant negative effect of a military burden on growth in the long run and short-run when aid is not included as an explanatory variable. Foreign aid increases the magnitude of the regression coefficients however there is no evidence that aid increases the military burden. Overall, the ARDL approach to cointegration supports the data and is effective at providing empirical proof to seemingly axiomatic statements on the military spending and growth relationship.